Profiling Malaysian youth philanthropy in professional volunteer organizations - Hamzah, Siti Raba'ah; Suandi, Turiman (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
This paper discusses the profiling of young Malaysian volunteers who were members of professional volunteer organizations. The subjects in the study were volunteers from 26 different volunteer organizations serving the community at local and international levels. Data for the study were collected via a questionnaire survey. There were 337 respondents, 225 of whom worked for local volunteer organizations while 112 were volunteers for international organizations. They were between the ages of 15 and 30 (M age = 22.8, SD = 5.65). Using the Volunteer Function Inventory (VFI) by the Fetzer Institute, six dimensions were extracted from the data following a factor analysis. These dimensions were then incorporated into a model of philanthropy and volunteerism based on the Social Capital theory. The estimates confirmed important reasons for volunteering, viz. intention to help others, charitable giving, activism, helping power motivation, and charity values. A factorial multivariate analysis of variance (MANOVA) revealed that the mean VFI factor scores were significantly different between volunteers for local and for international organizations. Follow-up analyses revealed that the volunteers working for international volunteer organizations displayed slightly higher scores in intention, activism, and helping power motivation in all six areas compared to those working with local community organizations. Implications from the findings are also discussed.